The new German Jewish literature Holocaust memory, solidarity, and worldliness - Taberner, Stuart 1969- (Camden House, 2025)
"Posits a New German Jewish Literature that has surprising implications for today's German Jewish - and Jewish - identity, including solidarity with others, even after October 7, 2023. Eighty years after the Holocaust, it is now possible to speak of a New German Jewish Literature. Emerging out of a community that, following the arrival of more than 200,000 people of Jewish ancestry from the former Soviet Union, is now vastly larger, increasingly diverse, and culturally vibrant, German Jewish writers are re-articulating what it means to be Jewish in the "land of the perpetrators." More generally, they are also rethinking Jewish values and Jewish solidarity against the backdrop of global events and trends such as the resurgence of antisemitism, the Israeli-Palestinian conflict, and growing intolerance towards ethnic, religious, and sexual minorities.
Keywords: German fiction / Jewish authors / History and criticism; German fiction / 21st century / History and criticism; Jews in literature; Identity (Philosophical concept) in literature; Memory in literature; Holocaust, Jewish (1939-1945), in literature; Worldliness in literature; Solidarity in literature; Roman allemand / Auteurs juifs / Histoire et critique; Roman allemand / 21e siècle / Histoire et critique; Juifs dans la littérature; Identité dans la littérature; Mémoire dans la littérature; Holocauste, 1939-1945, dans la littérature; Mondanité dans la littérature; Literary criticism; Critiques littéraires